Technical Guidance on Creating Digital Formative Assessments to Support the Implementation of the Merdeka Curriculum for Teachers at SMAN 1 Lubuk Sikaping - emiliannur, Emiliannur; Ratnawulan, Ratnawulan; Doni, Rahma (Pelita Eksakta, 2025)
Current technological advancements are driving changes in assessment practices. The teachers at SMA N 1 Lubuk Sikaping have not yet optimally implemented digital formative assessments. The Community Partnership Program in the form of technical guidance on creating digital formative assessments to support the implementation of the Merdeka Curriculum is needed by the teachers at SMA N 1 Lubuk Sikaping. This activity aims to motivate and assist Physics teachers in continuously improving their competencies, particularly in knowledge. This community service activity in the form of mentoring uses a method that consists of several stages. The first stage is the preparation stage, the second stage is the guided and independent activity stage, and the third stage is monitoring. This activity received a positive response from the participants, namely the teachers of SMA N 1 Lubuk Sikaping, with more than half of the participants stating that the training was interesting, beneficial, and effective.